Reintroductions and controlling feral predators: Interview with Per Christensen - Christensen, P.; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2013)
From tracking Antelope and other species in Kenya as a child, Per Christensen went on to train in ecology and participate in many of the key small mammal reintroduction programs in Western Australia. What lessons can be gleaned from these experiences for current and future restoration ecology? © 2013 Ecological Society of Australia.